Analysis Research Trends of Physical Literacy in Indonesia - Friskawati, Gita Febria; Stephani, Mesa Rahmi (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
In Indonesia, physical literacy has not developed as rapidly as in developed countries. There are only a few of studies examining physical literacy in Indonesia. This study was aimed to scientifically reveal the focus of physical literacy studies in Indonesia by using an article review approach. The search for articles was limited to the latest 10-year publications and articles published in accredited National/International Journals and National/International Seminars provided with ISBN. A total of 7 articles were selected for further analysis using synthesis techniques. The results of the study revealed that there were only six studies on Physical Literacy in Indonesia published in National Journals and National/International Seminars. The focus of the study on physical literacy research in Indonesia included the lead to the measurement of physical literacy and the development of physical literacy instruments in elementary schools (three studies), using learning approach to improve physical literacy (two studies), and the concept of physical literacy in Physical Education (one study). This study is limited to an article review. For further research, it is hoped that new research focusing on physical literacy studies, using a research method approach adapted to the research objectives, will emerge to develop concepts, measurements, and implementations of physical literacy programs in Indonesia.Â